Comparative water use of native and invasive plants at multiple scales: a global meta‐analysis - Molly A. Cavaleri; Lawren Sack (Ecology, 2010)
Ecohydrology and invasive ecology have become increasingly important in the context of global climate change. This study presents the first in‐depth analysis of the water use of invasive and native plants of the same growth form at multiple scales: leaf, plant, and ecosystem. We reanalyzed data for several hundred native and invasive species from over 40 published studies worldwide to glean global trends and to highlight how patterns vary depending on both scale and climate. We analyzed all pairwise combinations of co‐occurring native and invasive species for higher comparative resolution of the likelihood of an invasive species using more water than a native species and tested for significance using bootstrap methods. At each scale, we found several‐fold differences in water use between specific paired invasive and native species. At the leaf scale, we found a strong tendency for invasive species to have greater stomatal conductance than native species. At the plant scale, however, natives and invasives were equally likely to have the higher sap flow rates. Available data were much fewer for the ecosystem scale; nevertheless, we found that invasive‐dominated ecosystems were more likely to have higher sap flow rates per unit ground area than native‐dominated ecosystems. Ecosystem‐scale evapotranspiration, on the other hand, was equally likely to be greater for systems dominated by invasive and native species of the same growth form. The inherent disconnects in the determination of water use when changing scales from leaf to plant to ecosystem reveal hypotheses for future studies and a critical need for more ecosystem‐scale water use measurements in invasive‐ vs. native‐dominated systems. The differences in water use of native and invasive species also depended strongly on climate, with the greater water use of invasives enhanced in hotter, wetter climates at the coarser scales.